SC-LAMT: A Side-Channel Hardened Lightweight Protocol for Secure Wearable Medical Devices - Jumaa, Ghazwh G.; Muhsen, Atheer R.; Hamzah, Fatimah Nazar; Almaiah, Mohammed Amin; Shehab, Rami (Engineering, Technology & Applied Science Research, 2025)
With the emergence of Medical Internet of Things (MIoT) devices, new security and privacy challenges have also arisen, especially at the physical layer with Side Channel Attacks (SCAs) that can compromise sensitive patient data and cryptographic operations.s. Existing lightweight authentication schemes provide security at the expense of timing, power, and memory resources. This study presents a comprehensive vulnerability analysis of the LAMT protocol and shows that it is vulnerable to SCAs. It also introduces SC-LAMT, an SCA–resistant lightweight authentication protocol designed for constrained MIoT platforms. To make SC-LAMT resilient against passive and active physical layer attacks, it involves constant-time hashing, session-based key masking, and secure memory handling. An implementation on a Cortex-M4-based platform demonstrates that SC-LAMT achieves mutual authentication in 0.14 ms, using only 144 bytes during the communication, which is superior to state-of-the-art protocols. In more than 1000 session-simulated cases, SC-LAMT achieved anonymity, session key secrecy, and full timing and power-analysis resistance. The results of the security analysis demonstrate that it achieved 100% resistance against all tested SCA vectors, thus being a robust and efficient solution for secure MIoT deployments.